Evaluation of the Neogene depositional dynamics in the Malay-Tho Chu Basin based on seismic analysis: effects of local and regional tectonism and paleoclimatic variations - Tu-Anh, Nguyen; Fyhn, Michael B.W.; Boldreel, Lars O.; Abatzis, Ioannis; Nguyen, Huyen T. (Vietnam Journal of Earth Sciences, 2024)
Depositional environments in areas located near sea level are vulnerable to even subtle changes in both tectonism, climate and eustatic sea level. Sorting out mechanisms behind depositional changes in inner shelf-margins and epeiric seas is therefore far from straight forward. The epeiric Malay-Tho Chu Basin, located in the shallow Gulf of Thailand offshore Vietnam, contains a thick uppermost Oligocene to Recent post-rift succession. Based on 18000 km of 2D seismic profiles, the uppermost Oligocene-Recent succession is subdivided into six seismic sequences. Seismic facies mapping of each sequence complemented by information from industry completion reports of 14 wells document a gradual increase in marine influence from latest Oligocene through Middle Miocene time. The increased marine influence reflects the propagation and opening of the southwestern spreading arm of the East Vietnam Sea (South China Sea (East Sea)) combined with rapid subsidence in the Malay-Tho Chu Basin resulting from fast thermal relaxation following Oligocene rifting and amplified by mild fault-controlled subsidence in especially the western part of the area. From the latest Middle Miocene, slowed subsidence and regression occurred in association with uplift in the nearby southwestern East Vietnam Sea. From the latest Miocene, and during the Pliocene and Pleistocene, subsidence rates increased promoting marine conditions towards the East Vietnam Sea in the southeast. Meanwhile, Mekong River avulsion combined with hinterland uplift stimulated fluvial and alluvial deposition in the northern and western parts of the basin. The long-term depositional pattern was controlled primarily by tectonics, drainage evolution and climate. Meanwhile, flood- and delta plain deposits intercalated with stacked fluvial incisions, often filled by estuarine deposits, document short-lived environmental changes most likely controlled by eustatic sea level fluctuations. Such intervals developed during latest Middle Miocene to Pleistocene periods of slow subsidence or fast depositional rates and are interpreted to be the result of substantial eustatic sea level fluctuations.